Antidiabetic Management Strategies for Treatment of Polycystic Ovarian Syndrome - Nandikola, Jaya Raju; Rangnath Wayal, Sandesh; S., Vijayabanu; B.N., Ravindra; K.S., Keshava; Chatterjee, Arindam; Jaganmohan, C.; R. Bhise, Manish; Devarakonda, Surya (Journal of Neonatal Surgery, 2025)
Polycystic ovarian syndrome (PCOS) is a prevalent endocrine disorder characterized by metabolic and reproductive dysfunctions, with insulin resistance playing a central role. Antidiabetic drugs, particularly insulin sensitizers such as metformin, are essential in managing both metabolic and reproductive aspects of PCOS. This article explores the effectiveness of antidiabetic medications in PCOS management, focusing on metformin, GLP-1 receptor agonists, and DPP-4 inhibitors. The integration of these pharmacological agents with hormonal therapies, such as oral contraceptives, offers a comprehensive approach that targets both insulin resistance and hyperandrogenism. Additionally, the role of lifestyle interventions, including diet and exercise, is examined as a critical complement to pharmacotherapy. The article highlights the need for personalized treatment approaches and further research to optimize combination therapies for long-term outcomes. Ultimately, antidiabetic management strategies, when combined with hormonal and lifestyle modifications, represent a multifaceted approach to improving both metabolic and reproductive health in women with PCOS.